Praktik Pembiayaan Murabahah Terhadap Kesejahteraan Anggota Dalam Perspektif Hukum Ekonomi Syariah (Studi Kasus di Koperasi Simpan Pinjam dan Pembiayaan Syariah Bakti Huria Syariah Cabang Bone) - Juniasti, Reni; Hasibuddin, M.; Darmawangsa, Andi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the practice of murabahah financing at the Sharia Bakti Huria Syariah Savings and Loans and Financing Cooperative, Bone Branch and its impact on members' welfare from the perspective of sharia economic law. Murabahah financing is one of the widely used sharia financial products and is considered in accordance with sharia principles because it is free from usury and prioritizes justice. The research method used is a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the practice of murabahah financing in cooperatives is in accordance with sharia principles, upholding justice and transparency. This financing improves the welfare of members, expands access to capital, and strengthens public trust in sharia finance in a sustainable manner. This study provides recommendations for improving the quality of murabahah financing to support the sustainability of cooperatives and the welfare of members as a whole.